Rancang Bangun Manajemen Pemilahan Sampah Logam Dan Non-Logam Otomatis - Abdur Rozaq; Muhyiddin Zainul Arifin; Sujono Sujono (KH. A. Wahab Hasbullah University, 2021)
In general, sorting waste is still done manually by human hands. For example, it is still done manually by human hands to sort metal and non-metal waste from a pile of garbage. This results in less efficiency in terms of time and energy and also greatly impacts the health of oneself and others. With these conditions, one solution is to build a metal and non-metallic waste sorting system in the trash. The metal and non-metal waste sorting system that is made can sort metal and non-metal waste automatically because it is equipped with an inductive proximity sensor system which functions to detect metal waste plus a NodeMCU module which functions as a data sender of information on the weight capacity of the waste. With this automatic waste sorting system, waste can be sorted according to predetermined types of waste such as metal waste and non-metal waste.